104 activities that build : self-esteem, teamwork, communition, anger management, self-discovery, and coping skills - Jones, Alanna (Lusby, MD : Rec Room Pub., 1998)
Contains 104 games that prompt people to change their behaviors, increase interaction with others, start discussions, address issues, build relationships, and build skills in coping, teamwork, self-esteem, communication, anger management, and self-discovery.
"Formerly titled The Wrecking Ball"--Cover p. [4].
Includes index.
Adult
Keywords: Games in mental health education; Games; Social skills in children; Educational games; Games; Social skills in children